2005
DOI: 10.1038/sj.eye.6702099
|View full text |Cite
|
Sign up to set email alerts
|

Open globe injuries: factors predictive of poor outcome

Abstract: Objective Despite advances in ocular and orbital imaging, instrumentation, materials, and surgical procedures, the management of open globe injuries continues to pose difficult management dilemmas. In this retrospective study, we identify clinical characteristics and outcome of a series of open globe injuries presenting to a major UK centre. Method Operating department records were reviewed to identify all patients who had undergone repair of an open globe injury from 1 January 1998 to 1 January 2003 at the Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
168
10
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(222 citation statements)
references
References 17 publications
27
168
10
17
Order By: Relevance
“…Other studies on trauma epidemiology confirm a male predominance, with a male : female ratio varying between 1.25 and 5.5. 3,14,18,19 The male : female ratio in this study was 1.42. This may reflect the more aggressive characteristics of male behaviour even in childhood aged.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Other studies on trauma epidemiology confirm a male predominance, with a male : female ratio varying between 1.25 and 5.5. 3,14,18,19 The male : female ratio in this study was 1.42. This may reflect the more aggressive characteristics of male behaviour even in childhood aged.…”
Section: Discussionmentioning
confidence: 50%
“…3,4 Despite public health campaigns designed to prevent eye injuries, open globe injuries still occur. Identifying the causes and the nature of these injuries in the population, and directing educational and legislative efforts towards minimizing eye injury, are the previous goals of prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The incidence rates of ocular trauma requiring hospitalisation are reported to be 8.1 per 100 000 persons per year in Scotland, 2 12.6 per 100 000 persons per year in Singapore, 3 13.2 per 100 000 persons per year in the United States, 4 and 15.2 per 100 000 persons per year in Australia. 5 Several studies have suggested that the factors that significantly predict visual outcome after open globe injuries are initial visual acuity, 6,7 presence of a relative afferent pupillary defect (RAPD), 7,8 mechanism of injury, 7,9,10 wound location, 7,11,12 adnexal trauma, 8,13 lens damage, 7,12 hyphaema, 14 vitreous haemorrhage, 11,15 and retinal detachment. 11,16 In 2002, Kuhn et al 17 developed a prognostic model, the ocular trauma score (OTS), to predict the visual outcome of patients after ocular trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Para Fonseca (7) , a exérese do globo ocular representa aproximadamente 3,1% de todas as cirurgias oftalmológicas, havendo predominância do gê-nero masculino, principalmente devido à maior exposição ao trauma. Assim, o glaucoma (8) , traumatismos (9)(10)(11) e tumores intra-oculares têm sido considerados como etiologias importantes da anoftalmia (12)(13)(14) . O objetivo deste estudo foi avaliar o perfil das causas e das conseqüências biopsicossociais da perda do globo ocular, em pacientes sob reabilitação com próteses oculares, no Centro de Tratamento de Deformidades Crânio-Faciais -"Centrinho", da Universidade de Alfenas, Minas Gerais, Brasil.…”
Section: Resumo Introduçãounclassified